2010
DOI: 10.1016/j.brainres.2010.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic responses to SMS shortcuts

Abstract: As the popularity of sending messages electronically increases, so does the necessity of conveying messages more efficiently. One way of increasing efficiency is to abbreviate words and expressions by combining letters with numbers such as gr8 for "great," using acronyms, such as lol for "laughing out loud," or clippings such as msg for "message." The present study compares the processing of shortcuts to the processing of closely matched pseudo-shortcuts. ERPs were recorded while participants were performing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…This implies that the shortcuts were more difficult to recognize, but that their semantic processing did not differ much from that of words. This is in line with a recent study showing that shortcuts engage processes of semantic access similar to conventionally spelled words (Ganushchak, Krott, & Meyer, 2010a; see also Ganushchak, Krott, & Meyer, 2010b).…”
Section: Discussionsupporting
confidence: 91%
“…This implies that the shortcuts were more difficult to recognize, but that their semantic processing did not differ much from that of words. This is in line with a recent study showing that shortcuts engage processes of semantic access similar to conventionally spelled words (Ganushchak, Krott, & Meyer, 2010a; see also Ganushchak, Krott, & Meyer, 2010b).…”
Section: Discussionsupporting
confidence: 91%
“…The results showed that shortcuts were categorized as non-words more slowly than pseudo-shortcuts and that the N400 amplitude (270-500 ms) was more negative for pseudo-shortcuts than for shortcuts. Ganushchak et al's (2010) results suggested that shortcuts activated stored lexical representations of their basic words and that their semantic processing characteristics were therefore similar to those of standard words. Ganushchak et al (2012) used a masked priming lexical decision paradigm to compare the priming effects of shortcuts and their corresponding words (conventional forms).…”
Section: Introductionmentioning
confidence: 84%
“…This suggests that shortcuts are harder to recognize, but that, once recognized, they are integrated into the sentence context as easily as ordinary words. Additional evidence supporting this view comes from an event related potentials (ERP) study by Ganushchak et al (2010a). Here a lexical decision task was used.…”
Section: Introductionmentioning
confidence: 95%
“…Finally, between 250 and 400 ms after the word onset, lexical access takes place, as indexed by the N400 component (Kutas and van Petten, 1994; Kutas and Federmeier, 2000). Ganushchak et al (2010a) found that ERP responses for SMS shortcuts did not differ from those of pseudo-shortcuts until about 270 ms after stimulus onset. However, shortcuts and pseudo-shortcuts significantly differed from each other in the N400 window, suggesting that shortcuts, but not pseudo-shortcuts, activate stored lexical representations.…”
Section: Introductionmentioning
confidence: 99%